SISTEM INFORMASI LOGISTIK DAN PERALATAN PADA BADAN PENANGGULANGAN BENCANA DAERAH PAKPAK BHARAT BERBASIS WEB - Selly Yulita Hutabarat; Roni Jhonson Simamora; Eviyanti Novita Purba (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Management of the availability of goods that we know during this time is the provision of goods to see the activity of goods according to the conditions in the goods warehouse. However, in contrast to the conditions that exist, the BPBD Pakpak Bharat is still not optimal in the availability of logistics and equipment that can provide implementation needs at the time of arrival in the community. In order to provide the intended availability of BPBD Pakpak Bharat, this system was developed with the PHP and MySQL programming languages. This information system can also be used to process employed data at BPBD Pakpak Bharat as well as Logistics and Equipment that are in the Master Bar as a master-database that starts from the process of goods including traffic through the selection of goods according to the need for various types of disaster assistance that affect the community. Input of goods will be carried out on the employee's website from BPBD Pakpak Bharat who has reported everything that has been compiled according to Logistics and Goods that have been registered from the Head of Emergency and Logistics Subscription. The output in this information system is to provide logistics and equipment availability to see the readiness of the BPBD Pakpak Bharat in tackling a later plan.